INTERACTIVE INFORMATION MEDIA OF THE GENERAL ELECTION COMMISSION (KPU) OF EAST LOMBOK DISTRICT BASED ON ANDROID - Siti Hawari; Lalu Puji Indra Kharisma; Siti Rabi'atul Adawiyah; Anisa Muziya Rafa (JATISKOM : Jurnal Aplikasi Teknologi Informasi dan Sains Komputer, 2024)
The application of multimedia as information media has now expanded its use even to KPU information issues. The development of information technology, especially multimedia technology using android-based tools, can help the younger generation or the community in general in obtaining information on the East Lombok Regency General Election Commission in the existing KPU books, the younger generation or the community in general still feel some obstacles or problems such as how to find out East Lombok KPU information such as how to vote correctly, the history of the East Lombok KPU, KPU RI, temporary voter data (DPT). The purpose of this research is to create an Android-based General Election Commission (KPU) Information Media. It can be used to access East Lombok Regency election information and reduce election fraud. In this thesis, the author provides an alternative solution to the existing problems. These, namely several East Lombok KPU information media applications, can provide an overview or explanation in the form of text, images and videos. According to Luther Sutopo, the design and manufacture of the East Lombok KPU information media application based on Android use the multimedia development method, which consists of six stages: conceptualizing, design, material collecting, assembly, testing and distribution. The result or output of the application that the author designed is a packaged Android application.